The Social Ontology of Allamah Tabatabaei Based on Constructs (I'tibariat) - Hamid Hasani (آموزه‌‌های فلسفه اسلامي, 2022)
Social ontology is a field under applied metaphysics that studies the quiddity and attributes of social ontology. The main question is how the social world has been constructed which itself encompasses two questions: what are the constituent components of the social world and what factors have been established it? Allamah Tabatabaei has opinions about the issue of constructs (i'tibariat) and especially constructs after society (conventions) that seems to have a strong relationship with the subject matter. This article has aimed to extract his potential answers to this question from terminology and the conceptual structure of thinking. in this respect, it is firstly abbreviated Allamah Tabatabaei’s attitude about the formation of the social categories and then his opinion is compared with the existing theories. It seems that Allamah Tabatabaei believes that the components which constitute a community are the non-social components including constructs (i'tibariat) and mental states of the community such as cognitivism and thinks the factor which establishes social categories is a factor in the community scale (the agreement between two applications or more) that it is not necessarily “agreement” or “contract”.